The Emerald handbook of evidence-informed practice in education : learning from International Contexts - Brown, Chris; Malin, Joel R. (Emerald Publishing Limited, 2022)
Across many countries, national, federal and district level governments are increasingly pursuing approaches to school improvement that seek to achieve so-called 'bottom-up' change. That is, improvements to teaching and learning that are generated by teachers, and subsequently shared horizontally and vertically within educational systems. Often such change relies on educators engaging in 'evidence-informed practice': improvements to teaching in learning that are grounded in data and research. Within this context, this handbook examines how to bring about more consistent, evidence-informed practice in education globally. To do so, chapter authors have employed Hood's (1998) social regulation/cohesion matrix, combined with an institutional theory analytic lens, to provide detail on their specific contexts, including perspectives from every continent. Insights are subsequently analysed comparatively to provide generalisable insights that can be applied to any country, across the globe. Generating understanding into how to more routinely foster evidence-informed teaching practice globally, this ground-breaking handbook is vital reading for educational researchers, and especially those working close to practice, in all settings. It is hoped that there are also lessons from education that can be applied to other areas such as social care, justice or health.